Endoscopic treatment of biliary complications after living donor liver transplantation in a high volume transplant center in Turkey; a single-center experience - Harputluoglu, M.; Aladag, M.; Demirel, U.; Bilgic, Y.; Dertli, R.; Erdogan, M. A.; Yilmaz, S. (Univ Catholique Louvain-Ucl, 2018)
Background and aim : Biliary complications are an important cause of mortality and morbidity after living donor liver transplantation (LDLT). We present our endoscopic treatment results after LDLT as a single center with high volume. Methods : Patients who underwent endoscopic retrograde cholangiopancreatography (ERCP) alter LDLT between 2005 and 2015 were included. Clinical data included patient demographics. ERCP indications (stricture or leak), and treatment outcomes, including need for percutaneous and surgical interventions. Results : ERCP was performed in 446 (39.2%) patients with duct-to-duct anastomosis of 1136 LDLT patients. The most common biliary complication was stricture +/- stone (70.6%, 315/446). Stricture and leak occurred in 60 (13.4%) patients. Only binary leak was found in 40 (8.9%) patients. Our endoscopic treatment success rate in patients with biliary stricture after LDLT was 65.1%. Overall endoscopic success rates in our patients were 55.0% in patients with both leak and stricture, and only leak. In all, our percutaneous transhepatic biliary interventions (P'f BI) and ERCP success rate was 90.6% in patients with biliary complications after LDLT. Conclusions : Endoscopic treatments are highly effective for biliary complications after LDLT. Effective use of percutaneous interventions in collaboration with endoscopic treatments significantly reduces the need for surgical treatment.
Keywords: Liver transplantation; biliary complication; endoscopic retrograde cholangiopancreatography